Analysis of Factors Affecting Teacher Performance in State Junior High School Learning in Bengkalis Regency - Melly Miranda; Almasdi Syahza; Sumarno Sumarno (Universitas Riau, 2021)
This study aims to analyze the factors that influence the performance of teachers in learning SMP Negeri in Bengkalis Regency. The population sample in this study is amounted to 56 people. They are all teachers who are Civil Servants who teach at Bengkalis Regency Public Junior High Schools consisting of Public Junior High Schools in Bukit Batu District and State Junior High Schools in Bandar Laksamana District. Data was collected using a questionnaire. The data analysis used in this research is descriptive quantitative and path analysis. The results of the study show: 1) the work climate has an effect on teacher job satisfaction by 43.1%; 2) work motivation has an effect on teacher job satisfaction by 42.5%; 3) work climate has an effect on teacher performance by 35.3%; 4) work motivation has an effect on teacher performance by 32.7%; 5) job satisfaction has an effect on teacher performance by 26.0%; 6) work climate has an effect on teacher performance through job satisfaction of 11.2%; 7) work motivation has an effect on teacher performance through job satisfaction of 11.0%. The meaning is that if the work climate has good quality, is comfortable, and pleasant, it will lead to satisfaction for a teacher, and this will trigger the teacher's enthusiasm in teaching which will have an impact on improving teacher performance.